The factors that lead to customer satisfaction towards online banking services among the students in University of Science Malaysia (USM), Penang / Syifa Nabiha Syamsul Faiz and Nur Izzati Othman - Syamsul Faiz, Syifa Nabiha; Othman, Nur Izzati (2019)
This chapter focuses on the study of the customer satisfaction towards online banking. It begins with the background of the study for the online banking system and followed with the problem statement, research questions, research objectives, scope of study and the definition of terms, terminology and concepts of the dependent and independent variables used in this research study.